EFFECT OF GARLIC EXTRACT ON SMALL INTESTINE TO INCREASE INTERFERON γ IN WHITE MALE BALB/C MICE - Sunaryati, Titiek (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2012)
Common cold is an infectious disease that is caused by viruses. The purpose of this study is to explain how garlic extract can increase body  immunity.     This was experimental study using white male BALB/c strain mice, 10 weeks old with bodyweight of 25-35 grams. Group 1 received placebo (CMC Na) for 14 days. Group 2 received 10mg/kg BW garlic extract for 14 days, and group 3 received 20mg/kg BW garlic extract for 14 days. After 14 days mice were sacrified then  intestines were removed and processed in the paraffin block, then were stained with immunohistochemistry.     There was one  variable such as the amount of cell that produce interferon γ. Data were analyzed by analysis of variance Brown Forsythe, any significant different was further analyzed by using Games Howell in the significant level of 0.05. There were significant difference between groups those received placebo, 10mg/kgBw garlic extract, and 20mg/kgBw garlic extract in each variables.     Garlic extract can increase body immunity via increase in the amount of cell that produce interferon γ.